What patients judge as important regarding nursing quality: Content analysis of patients' responses to an open-ended question within an online survey - Kirchner-Heklau, Uta; Meyer, Gabriele; Fleischer, Steffen (Pflege, 2022)
What patients judge as important regarding nursing quality: Content analysis of patients' responses to an open-ended question within an online survey In a cross-sectional study with people insured by a health insurance company the association between the quality of care assessed by patients and nurse staffing in acute care hospitals has been investigated. A systematically developed online questionnaire registered the patients' assessments of nursing care, nursing behavior and nursing outcomes. The questionnaire included an open-ended question that was designed to supplement other important aspects where appropriate. Which aspects of the experienced care were particularly important for the patients but were -from their point of view- not yet covered by the questionnaire? Can additional indicators of care quality be derived? Online survey following hospital discharge. Content analysis of the free text entries to the open-ended question. A total of 212554 insured people were contacted; 30209 participated in the survey (14,2%) and 12507 (41,4%) of them answered to the open-ended question. A random selection of free text replies ( =2000) was finally coded and analyzed. Altogether, 45,1% of all codes covered the aspects of care quality included in the questionnaire. Of the remaining codes, 35,1% contained statements about non-nursing quality aspects of hospitalization and 19,8% contained statements about working conditions. No additional indicators of quality of care could be identified. The statements about the working conditions will be explored in a further analysis. The expectations of patients towards nursing care need to be investigated in future studies.